Experience Gained In Mechanical And Conventional Excavations In Long Alpine Tunnels In Switzerland - Y. Boissonnas (Society for Mining, Metallurgy & Exploration)
INTRODUCTION, The transalpine rail routes in Switzerland are well over one hundred years old. As the established routes no longer meet the demands of the continually increasing volumes of rail traffic between north and south, two new routes through the Alps were planed. The old Gotthard rail line is in fact a mountain railway. The northern and the southern access ramps?with a maximum speed of 80 km/h and a maximum slope of 2.2%?reach the old Gotthard rail tunnel at an elevation of approximately 1,100 m above sea level. This is approximately 900 m higher than the city of Milan. In 1992, the Swiss electorate people voted with an overwhelming majority in favor of the project to build the new base routes through the Alps. The Swiss voted again in 1998 in favor of the financing proposal for the new infrastructure. Swiss Federal Railways together with the BLS Lötschbergbahn were commissioned for the realization and management of the Gotthard and Lötschberg routes. AlpTransit Gotthard Ltd., founded by Swiss Federal Railways, was given the task of managing the design and realization of the Gotthard route until the start of regular service. In the meantime the shorter Lötschberg Base Tunnel was open to traffic in 2007